The Study of Paddy Drying in Zig Zag Pipe Spouted Bed Dryer - Wongbubpa, Nuttapong; Chitsomboon, Tawit (Srinakharinwirot University Engineering Journal, 2022)
The objective of this research was studied on the drying potentiality of paddy in Zig - zag piped spouted bed dryer. The prototype of the dryer was designed and fabricated in the modern concept which can rapidly dry according to the enforcement of paddy flow in the test section. This technique is used to provide the extended drying period and well mixing of paddy and hot air in the dryer which affected in reducing the drying time and increasing in energy consumption efficiency in the dryer. The 4 kg Khao Dawk Mali 105 rice specie paddy is testing material mixing. Using the 80°C, 100°C and 120°C hot air as the working fluid at the air velocity of 16 m·s-1. Two type of the 90° elbow test section (8 and 16 turning elbow) are used in this experiment. The experimental results show that at high air temperature 16 turning elbow pipe performs higher drying rate and consumes lower primary specific energy (SECHeater) than 8 turning elbow pipe. While 8 turning elbow pipe gives lower secondary specific energy (SECBlower) than 16 turning elbow pipe. The lower hot air temperature required the more activated energy in evaporating the moisture of paddy grain than higher hot air temperature. Likewise, 8 turning elbow test section yields more activated energy than 16 turning elbow test section. As the activated energy of 43.78 to 170.74 kJ·mol-1 were used in this experiment.